GIC-LAC regional workshop strengthens capacities for agriculture and land-use emissions reporting - Haynes, Connor; Yomayuza, Karoll Valentina (2025)
How can Latin American countries demonstrate their commitment to climate action? Representatives from Mexico, Colombia, Guatemala, Honduras, and El Salvador met in Guatemala City for the GIC-LAC Regional Workshop in 2025. Over three days, they shared experiences and developed strategies to improve how their country monitors and reports greenhouse gas (GHG) emissions from the agricultural and the land use, land-use change and forestry (LULUCF) sectors.